Determination of swertiamarin and amarogentin content and evaluation of antibacterial activity in Eastern Himalayan species of Swertia L. - Samaddar, Tapojita; Chaubey, Binay; Jha, Sumita; Baran Jha, Timir (Pharmacognosy Communications)
Introduction: The genus Swertia is known to contain many bioactive compounds having pharmacological activities. Biochemical fingerprinting can be useful in screening elite populations within and between Swertia species. The present work reports the estimation of two important bioactive compounds: swertiamarin and amarogentin and the evaluation of antibacterial activities in different species of Swertia collected from Eastern Himalayan regions of India. Methods: Chromatography was performed using a CAMAG HPTLC system for estimation of swertiamarin and amarogentin in S. chirayita, S. bimaculata, S. dilatata, S. nervosa and S. paniculata, collected from different regions of Eastern Himalayas. Separation was carried out on thin-layer chromatography aluminium plates pre-coated with silica gel 60 F254, eluted with ethyl acetate-methanol-water (77:15:8 v/v/v). Antibacterial activity against selected human clinical pathogens was tested by the disc diffusion method. Results: This investigation reports for the first time, the presence of swertiamarin in S. dilatata which is conventionally considered as an adulterant species in the chirata trade. The high quantity of swertiamarin detected in S. bimaculata leaves (5.80%) of Mungpoo population suggests that this so called inferior species can be a potential and promising source of swertiamarin in herbal and pharmaceutical industries. Antibacterial activity against Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa was observed in swertiamarin and amarogentin and in the plant extracts. Conclusions: Synthesis of swertiamarin in reproductive shoots of S. bimaculata, S. nervosa, S. dilatata and S. paniculata may provide a new source of biomass for future use. Activity against selected bacteria tested revealed promising antibacterial potential of the extracts of Swertia.
Keywords: Amarogentin; antibacterial activity; Eastern Himalayas; high performance thin layer chromatography; Swertia species; swertiamarin